2018
DOI: 10.20902/ijctr.2018.111124
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of LC-MS/MS method for the estimation of Droxidopa in Human Plasma

Abstract: A high performance liquid chromatography mass spectrometric method for the estimation of droxidopa in human plasma in positive ion mode was developed and validated using levodopa as internal standard (IS). Sample preparation was accomplished by solid-phase extraction technique. The eluted samples were chromatographed on Hypurity advance, 4.6*50mm, 5µm (Thermo Scientific) column using a mobile phase consisting of 0.1% formic acid and methanol (80:20, v/v).The method was validated over a concentration range of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A literature survey reveals that only one method based on HPLC (Ankit et al, 2017) is available for determination of droxidopa in the formulation and HPLC and LC-MS/MS (Chen and Hewitt, 2018;Derangula et al, 2018;Wang et al, 2016) methods have been reported for estimation of drug and its metabolites in biological luids. These methods are complicated, costly, and time-consuming with complicated mobile phases and gradient elution, leading to baseline shifting in comparison to a simple HPLC-UV process.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey reveals that only one method based on HPLC (Ankit et al, 2017) is available for determination of droxidopa in the formulation and HPLC and LC-MS/MS (Chen and Hewitt, 2018;Derangula et al, 2018;Wang et al, 2016) methods have been reported for estimation of drug and its metabolites in biological luids. These methods are complicated, costly, and time-consuming with complicated mobile phases and gradient elution, leading to baseline shifting in comparison to a simple HPLC-UV process.…”
Section: Introductionmentioning
confidence: 99%